Trail without Catheter after Transurethral Resection of Prostate: Clamp It or Not? - Vikash Talreja; Aun Ali; Summaya Saeed; Kiran Rani; Sunil Sadruddin Samnani; Farah Naz Farid; Mumtazuddin Haider (Scientifica)
Background. There has been argument between clinical practitioners about clamping catheter or not prior to its removal after transurethral resection of prostate (TURP). We conducted a clinical trial to assess whether clamping has any role in early bladder tone recovery particularly in patients who undergo TURP. Methods. Randomized clinical trial was conducted at a tertiary care hospital, Karachi from January 2014 to July 2015. Eighty-six study participants who underwent TURP were randomly allocated into two groups of 43 participants each. In Group I, patient’s Foley catheter was not clamped prior to its removal and in Group II Foley catheter was clamped. Data of all subjects were analyzed using SPSS version 20. Results. There was no significant difference in age and weight of resected tissues between two groups. Among 4 patients in Group I who required recatheterization, 1 patient was discharged with catheter as compared to Group II in which 2 patients were discharged with catheter (P=0.99). Only 1 patient (2.3%) in Group II had bleeding which required recatheterization. Length of stay was significantly affected by early and free removal of Foley catheter (P<0.001). Conclusion. The results of current study identified that clamping whether done or not had no significant impact on urinary retention.